Islamic Business Ethics Practice among Muslim Entrepreneurs in Kano Metropolis, Nigeria - Sulaiman, Sagir Muhammad; Muhammad, Aliyu Dahiru; Sabiu, Tasiu Tijjani (Universitas Muhammadiyah Yogyakarta, 2020)
There are persistent increasing number of scenarios in Singer and Dawanau markets of Kano metropolis which are seen as unethical among which includes deception, inappropriate weight and measures, hoarding and price manipulation as well as false-swearing to support a sale. This study therefore assesses the determinants of Islamic business ethics practices among Muslim entrepreneurs in Kano metropolis, Nigeria. Structural Equation Modelling (SEM) technique is employed in analysing the hypothesized model of the study. The results indicate that entrepreneurs fairly adhere to Islamic business ethics practice while legal and organizational factors significantly affect Islamic business ethics, but Individual factors do not. The study recommends the need for Kano State Ministry of Commerce and Industry in collaboration with market organizational leaders to engage in public enlightenment on the importance of business as an act of worship (Ibadat). It was suggested that organization leaders i.e. Market leaders (trade union leaders) should liaise with Kano state Shariah Commission to set standard for Islamic business ethics whereas Hisbah Board to enforce compliance. The study further suggests that the concept of ethics should be incorporated in teaching and learning curriculum.